2017
DOI: 10.3892/mmr.2017.6753
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Huaiqihuang on hyperglycemia-induced MPC5 podocyte dysfunction through the suppression of mitochondrial dysfunction and endoplasmic reticulum stress

Abstract: The present study was performed to investigate the effect of Huaiqihuang (HQH) on hyperglycemia (HG)-induced mitochondrial dysfunction and endoplasmic reticulum (ER) stress in MPC5 podocytes. The effects of HQH and HG on cell viability were assessed using an MTT assay. mRNA and protein expression levels were evaluated using reverse transcription-quantitative polymerase chain reaction and western blot analysis, respectively. Cell apoptosis was assessed using terminal deoxynucleotidyl transferase deoxyuridine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…When MPC5 podocytes were cultured in a high glucose medium, intracellular Ca2+ and ROS levels increased significantly, leading to mitochondrial dysfunction. Li et al [12] showed that Huaier can improve the mitochondrial membrane 2…”
Section: Regulation Of Oxidative Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…When MPC5 podocytes were cultured in a high glucose medium, intracellular Ca2+ and ROS levels increased significantly, leading to mitochondrial dysfunction. Li et al [12] showed that Huaier can improve the mitochondrial membrane 2…”
Section: Regulation Of Oxidative Stressmentioning
confidence: 99%
“…It also has the ability to inhibit inflammatory cytokine expression like IL-6 and macrophage infiltration [11]. The oxidative stress levels are suppressed with decreased Ca 2+ and ROS expression in podocyte [12]. By means of autophagy, HQH balances the activity between mTOR and HQH [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations